A Short Media History of English Literature - Berensmeyer, Ingo (De Gruyter, 2022)
This book explores the history of literature as a history of changing media and modes of communication from prehistory to the present. It argues that literature has evolved, and continues to evolve, in sync with material forms and formats that engage our senses in multiple ways. In telling the story of these connections, it combines an unusual bird's eye view across periods with illuminating readings of texts from (mostly) English literature.